SISTEM PAKAR UNTUK MENDIAGNOSA HAMA DAN PENYAKIT TANAMAN TOMAT MENGGUNAKAN METODE FORWARD CHAINING - Istanto, Agus Edi; Dewa, Weda Adistianaya (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
Tomato (solanum lyco persicum) are a pland of solanceae family, native plants of centeral and sount America, from meksico and peru. Tomatoes have a short life cycle and height from I up to 3 meters. Nowadays farmers often ignoie about to the pest and direases of tomatoes because of lack of know ledge. They also considered itâs eventually happen in planting fase, experts in tomatoes pest and diseases were umited, less dissemination from agricultural staff about pest and diseases in tomatoes, how ever they didnât know to control it and to eliminated fastor cawses decceased productivity.This study was using Forward ChainingÂ  method it is a description that starts from the know facts and then match it with IF and rules IF-THEN passage.Pert and diseases with high prevalences in tomatoes are pert: for a pert is Ulat buah, Ulat tanah, Kutu daun hijau, Lalat putih, Lalat buah (bractrotera) and then a diseases is a: Layu fusarium, Penyakit Bercak Daun, Bercak bakteri, Busuk buah .This expert system application provider information tomatoes pert and diseases diagnose, including controlling solution that can be used to reduce of minimize the risk of tomatoes plants damage.Â Keywords : System Expert, Diagnoses Pert And Diseases, Tomato.